2018
DOI: 10.20914/2310-1202-2018-2-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Study of the cattle blood concentrating

Abstract: The urgency of more complete use of food blood of slaughter animals is due to the content of protein substances in it with a high digestibility of the organism, in terms of its content it can be equated to meat. However, the part of the processed and used blood for food purposes is only 3% by the meat processing industry. Using of the slaughter animals blood in concentrated form allows its use as one of the most important sources of animal origin protein and a number of other substances necessary for human bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…2 -4) were of special interest. The analysis of the obtained graphical dependencies showed that the operating characteristics of the screw crystallizer for all values of the refrigerant boiling point in the heat exchange jacket of the crystallizer, the screw rotation speed and the initial content of dry substances in the plasma during concentration had a similar form [6][7][8][9].…”
Section: Results and Their Discussionmentioning
confidence: 97%
“…2 -4) were of special interest. The analysis of the obtained graphical dependencies showed that the operating characteristics of the screw crystallizer for all values of the refrigerant boiling point in the heat exchange jacket of the crystallizer, the screw rotation speed and the initial content of dry substances in the plasma during concentration had a similar form [6][7][8][9].…”
Section: Results and Their Discussionmentioning
confidence: 97%